2022
DOI: 10.1037/dev0001372
|View full text |Cite
|
Sign up to set email alerts
|

Executive function mediates the association between cumulative risk and learning in Ghanaian schoolchildren.

Abstract: Research on the associations among adversity, executive function (EF), and academic outcomes in lowand middle-income countries, where developmental risk factors are more prevalent and impoverished environments are more widespread than in high income countries, is sparse. This study examines the relations among cumulative risk, EF, and learning outcomes measured 2-years later in Ghanaian third-and fourth-graders (N = 371; 49% female), shedding light on underlying mechanisms of how risk can undermine learning. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 77 publications
2
8
0
Order By: Relevance
“…Similarly, Waters et al (2021) found that working memory, a specific EF skill, mediated relations between preschool parent education and first-grade math achievement. Finally, our study is in line with the one other study examining EF as a mediator between cumulative risk and learning outcomes (Suntheimer et al, 2022). In that study, results indicated that EF measured at age 9 significantly mediated the effect of cumulative risk from birth to age 9 on math achievement at age 11.…”
Section: The Role Of Ef and Behavioral Regulation In Relations Betwee...supporting
confidence: 91%
See 2 more Smart Citations
“…Similarly, Waters et al (2021) found that working memory, a specific EF skill, mediated relations between preschool parent education and first-grade math achievement. Finally, our study is in line with the one other study examining EF as a mediator between cumulative risk and learning outcomes (Suntheimer et al, 2022). In that study, results indicated that EF measured at age 9 significantly mediated the effect of cumulative risk from birth to age 9 on math achievement at age 11.…”
Section: The Role Of Ef and Behavioral Regulation In Relations Betwee...supporting
confidence: 91%
“…For example, studies have shown that EF during early and middle childhood mediates relations between socioeconomic factors and later academic outcomes (Deer et al, 2020; Lawson & Farah, 2017; Waters et al, 2021). Furthermore, in a recent study looking specifically at cumulative risk, results indicated that EF measured at age 9 significantly mediated the effect of cumulative risk exposure from birth to age 9 on math achievement at age 11 among Ghanaian children (Suntheimer et al, 2022). Thus, it is expected to do the same in models examining earlier cumulative risk and later educational outcomes.…”
Section: Cumulative Risk Exposure and Adolescent And Adult Health And...mentioning
confidence: 98%
See 1 more Smart Citation
“…Here we ask how household SES relates to EF and literacy skills for children in rural Côte d'Ivoire. Indeed, the negative association between low SES and academic outcomes, including literacy, has previously been found to be mediated by the development of EF both in LMICs and HICs (Dilworth-Bart, 2012;Ferguson et al, 2013;Lawson & Farah, 2017;Nesbitt et al, 2013;Suntheimer et al, 2022). We test the hypothesis that EF mediate the association between SES and literacy.…”
Section: Introductionmentioning
confidence: 88%
“…The majority of this research has focused on links between children's exposure to adversity and their own neurodevelopmental outcomes (e.g., Chahal et al., 2022; Demir‐Lira et al., 2016; Miller et al., 2020; Sheridan et al., 2017). For example, altered prefrontal cortex (PFC) development and difficulties in executive functioning are frequently documented outcomes in children exposed to adversity (Hanson et al., 2012; Pechtel & Pizzagalli, 2011; Suntheimer et al., 2022).…”
Section: Introductionmentioning
confidence: 99%